OPEN AIR CINEMA SEBAGAI RUANG KOMUNIKASI - Arifianto, Budi Dwi; Muktaf, Zein Mufarrih (Jurnal Publisitas, 2019)
Open air cinema is also called "layar tancap" is an exhibition style of film that plays in open space. Desa Sumber is in Magelang, Central Java, building a creative tourism village. The initial stage is exploring village potential as a commodity that will be offered as a tourist attraction. Film is considered to be a solution to answer these problems. Film as an art product was chosen as a medium for human empowerment, especially the medium to develop village potential. The purpose of this study was to find out the practice of open air cinema as a space for dialogue and communication in Sumber Village. The research method used is using the PRA (Participatory Research Appraisal) approach. Data retrieval by interview and participatory observation. The conclusion in this study is that film exhibition with an open air cinema model can be a medium of community communication. Film production and exhibition can support democratic communication relations.